DETERMINAN PENGHENTIAN PREMATUR ATAS PROSEDUR AUDIT : (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK YANG ADA DI JAKARTA SELATAN DAN JAKARTA TIMUR) - Bambang Subiyanto; Kumba Digdowiseiso; Muhammad Aufa Pumuka (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to analyze the Effects of Time Pressure, Quality review and control procedures, and Ethical Awareness on Premature Termination of Audit Procedures. The study was conducted on auditors who work at the Public Accounting Firm in South Jakarta and East Jakarta. The population in this study were auditors who worked at 10 public accounting firms in South Jakarta. The research method used is simple random sampling method. Based on this method, a total sample of 109 auditors was obtained, while 101 auditors were willing to be respondents. The data in this study are primary data obtained through questionnaires (questionnaires) which are distributed directly by visiting the Public Accounting Firm. The data analysis method used is statistical analysis in the form The results of this study indicate that time pressure has a significant effect on premature termination of audit procedures, this is evidenced at a significance level of 0.000 less than 0.05. Quality review and control procedures also has a significant effect on Premature Termination of Audit Procedures, this is evidenced at a significance level of 0.000 less than 0.05. Likewise, Ethical Awareness also has a significant effect on Premature Termination of Audit Procedures, this is evidenced at a significance level of 0.000 less than 0.05.